2017
DOI: 10.1002/cpt.892
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the CYP2B6 3′UTR Alter In Vitro and In Vivo CYP2B6 Activity: Potential Role of MicroRNAs

Abstract: CYP2B6*6 and CYP2B6*18 are the most clinically important variants causing reduced CYP2B6 protein expression and activity. However, these variants do not account for all variability in CYP2B6 activity. Emerging evidence has shown that genetic variants in the 3'UTR may explain variable drug response by altering microRNA regulation. Five 3'UTR variants were associated with significantly altered efavirenz AUC (8-OH-EFV/EFV) ratios in healthy human volunteers. The rs70950385 (AG>CA) variant, predicted to create a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…An increasing body of evidence demonstrates that small, noncoding RNAs, ranging between 20 and 24 nucleotides in length, provide an additional layer of regulation on the expression of drug metabolizing enzymes including CYPs [ 46 , 47 , 48 ] and that sequence variation in miRNA binding sites can perturb this mechanism as exemplified in vitro and in vivo by Burgess et al for the regulation of CYP2B6 expression [ 49 ]. Consistent with the finding that miRNA binding sites are often located in the 3’UTR region, the most prominent examples of CYP regulation by miRNAs involve binding sites in this region [ 49 , 50 , 51 , 52 , 53 ]. A bioinformatic search using 15 databases revealed that the 75 bp long 3’UTR of CYP2D6 contains a number of potential miRNA binding sites [ 47 ]; however, the author also indicated that this relatively small region does not harbor any known sequence variations that may interfere miRNA-mediated regulation.…”
Section: Genetic Factors Impacting Mrna and Protein Expression Levmentioning
confidence: 99%
“…An increasing body of evidence demonstrates that small, noncoding RNAs, ranging between 20 and 24 nucleotides in length, provide an additional layer of regulation on the expression of drug metabolizing enzymes including CYPs [ 46 , 47 , 48 ] and that sequence variation in miRNA binding sites can perturb this mechanism as exemplified in vitro and in vivo by Burgess et al for the regulation of CYP2B6 expression [ 49 ]. Consistent with the finding that miRNA binding sites are often located in the 3’UTR region, the most prominent examples of CYP regulation by miRNAs involve binding sites in this region [ 49 , 50 , 51 , 52 , 53 ]. A bioinformatic search using 15 databases revealed that the 75 bp long 3’UTR of CYP2D6 contains a number of potential miRNA binding sites [ 47 ]; however, the author also indicated that this relatively small region does not harbor any known sequence variations that may interfere miRNA-mediated regulation.…”
Section: Genetic Factors Impacting Mrna and Protein Expression Levmentioning
confidence: 99%
“…The effect of a genetic variant (rs12979270), located in the 3′ UTR of the pharmacogene- CYP2B6, was shown to be statistically significant in HepaRG cells. A recent study shows that this variant, could explain part of the interindividual variability seen in the activity of this critical pharmacogene ( Burgess et al, 2017 ). These results demonstrate the potential of this assay to identify clinically relevant functional genetic variants.…”
Section: Resultsmentioning
confidence: 99%
“…Studies profiling circulating miRNAs in liver diseases have shown that the expression of several miRNAs measured in plasma are upregulated or downregulated in liver diseases along with changes in CYP activity 18 . In vitro studies support a role of miRNAs in the regulation of CYP2B6 21 . In addition, exchange of miRNA between liver and blood may result in an association between circulating miRNA concentrations and hepatic CYP2B6 activity.…”
mentioning
confidence: 78%